Progress and Prospects of Chemical Functionalization of Textiles Via Nanotechnology - Hossain, Md. Tanvir; Reza, Selim; Islam, Md. Ariful; Mohebbullah, Md; Islam, Tarikul (ACS applied engineering materials, 2025)
Over the past decade, nanotechnology has gained considerable attention among academia and industry professionals, playing a pivotal role in advancing this sector. Chemical functionalization of textiles using nanotechnology has ushered in an era of advanced materials with superior properties and functionalities. This Review delves into the current progress and future prospects in this rapidly evolving field, focusing on key advancements such as antimicrobial properties, UV protection, self-cleaning capabilities, enhanced mechanical strength, and smart textiles. This Review provides a comprehensive overview of the past 15 years of advancements in functional textiles using nanotechnology. Several types of nanomaterials based on their dimensions and functionalities have been discussed and summarized. Fabrication techniques such as electrospinning, coating technologies, and printing methods have enabled the integration of nanomaterials into textiles, offering benefits like improved strength, durability, and functionality. While nanotechnology has brought about significant positive environmental impacts by enhancing textile properties and functionality, there are also concerns regarding potential adverse environmental impacts due to nanomaterial leaching. The Review highlights the collaborative efforts of academia and industry professionals in developing mitigation strategies and the exploration of biodegradable nanomaterials, which are being used to address these challenges, reassuring the audience of the industry.